THE EFFECT OF NANO-IRON CHELATED FERTILIZER ON AGRONOMIC ASPECTS OFMILLET-COWPEA INTERCROPPING - M. Sabeki; M. R. Asgharipour; A. Ghanbari; K. Miri (Journal of Animal and Plant Sciences, 2018)
This study was conducted to evaluate the effects of spraying of nano-iron chelate on millet-cowpea intercropping with regard to the importance of nano-chelates in improving crop yield and environmental preservation and to achieve sustainable agriculture goals. The experimental design was split based on randomized complete block design with three replications during 2015, at research field of Agriculture and Natural Resources of Bampour, Iran. Spraying of nano- chelated iron at 0, 1, 2 and 30 in two stages of branching and flowering comprising main-plots and 5 cropping systems including; millet sole culture, cowpea sole culture, 100% millet+20% cowpea, 100% millet+ 40% cowpea and 100% millet+ 60% cowpea. Results indicated that interaction of nano-iron chelate and cropping systems was significant on all studied traits (except leaf number of both crops and LER). Mean comparison revealed that the greatest millet grain yield -1 was obtained from plant sprayed with nano-iron at concentration of 30 and millet sole culture equals to 1021.33 kg ha and the lowest millet grain yield was obtained from non-sprayed plant and 100% millet+20% cowpea equals to 442.83 -1 kg ha .The results of the experiment confirmed that nano-iron chelated was effective on intercropping of millet and cowpea, so that plant sprayed at concentration of 30 had greatest morphological characteristics and yield of the both crops. millet has risen mainly because of important
Keywords: Cereal-legume intercropping; Nano fertilizer; Iron concentration; LER.